Early and Middle Wisconsinan Environments of Eastern Beringia: Stratigraphic and Paleoecological Implications of the Old Crow Tephra - Schweger, Charles; Matthews, John (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1985)
ABSTRACTThe widespread Beringian Old Crow tephra occurs in Imuruk Lake (Alaska) core V, above the Blake paleomagnetic event and below Radiocarbon dates, which provide an extrapolated tephra age between 87 000 - 105 000 BP. Exposure KY-11 (Alaska), where the tephra occurs in a dated lacustrine sequence, provides corroboration. Fossil pollen records show that O.C.T. was deposited across northern Beringia on birch-shrub tundra vegetation during an interval of colder climate. A series of climatic oscillations followed tephra deposition. A prolonged period of cold-arid climate ( = marine isotope Stage 4) preceded an interval of warmer than present climate starting ca. 60 000 BP (beginning Stage 3). During this interval, designated the Koy-Yukon thermal event, an exposed Bering land bridge promoted an interglacial type climate that led to significant biotic changes and permafrost degradation. O.C.T. occurs on drift of the Mirror Creek Glaciation which is equivalent to other presumed Early Wisconsinan glaciations in Alaska and Yukon. These glaciations could not have occurred later than marine Stage 5. Stage 4 was fully as cold as Stage 2 (Late Wisconsinan), yet seems not to have been a time of extensive glaciation. The Middle Wisconsinan, 30 000 to more than 80 000 BP, was a nonglacial interval with several climate fluctuations, one of which, the Koy-Yukon thermal event, was warmer than at present.